Diversity of Soil Inhabiting Arthropods in Intercropping of Chili and Chinese Mustard Green Applied With Bacillus thuringiensis Based Bio-Insecticides and Synthetic Insecticides Treatment - Fitri Sunarsih; Yulia Pujiastuti; Mulawarman Mulawarman (Sriwijaya Journal of Environment, 2020)
Bio-insecticide is one of alternative ways in controlling plant pests with many advantages compared to synthetic insecticides, especially in environmental aspects. Bacillus thuringiensis is a microbial agent which most widely used as bio-insecticide to control insect pests belongs to Filum Arthropods. Biodiversity of arthropods in intercropping plants with application of B. Thuringiensis based bio-insecticide was investigated. Chili and mustard chinese green intercropped in which chili was one season and the other was two seasons. B. thuringiensis-based bio-insecticide and chemical insecticide were applicated on those plants. Sampling of arthropods were conducted by pitfall trap and yellow pan trap The result showed relative abundance of arthropods was higher in Bt B. Thuringiensis-based bio-insecticide treatments compared with chemical one. Dominance Index of second season was higher than in first season. Index of evenness resulted no difference (E < 0.5) between first season and second season shows that population level of each species was not different.